Food Safety Regulations and Their Impact on Public Health (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to provide a thorough examination of food safety regulations and their profound impact on public health. The study delves into the multifaceted aspects of regulatory frameworks at local, national, and international levels, emphasizing their role in preventing foodborne illnesses and ensuring the overall well-being of the population. By exploring microbial and chemical safety, allergen management, good manufacturing practices, and other critical components, the paper aims to elucidate the various ways in which food safety regulations contribute to a safe and secure food supply chain. Additionally, the research scrutinizes the effectiveness of hazard analysis and critical control points (HACCP), traceability systems, and recall procedures in responding to potential threats. Through a comprehensive review of literature, case studies, and statistical data, this paper seeks to provide insights into the practical implications of food safety regulations and their tangible impact on public health outcomes.